2006
DOI: 10.1016/j.agwat.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate accumulation and movement under deficit irrigation in soil receiving cattle manure and commercial fertilizer

Abstract: Nitrate leaching from agricultural soils can increase groundwater nitrate concentrations. The objectives of the study were to assess the accumulation and movement of nitrate in the soil profile over a 2-year period under deficit irrigation conditions following a one time application of N in cattle feedlot manure and commercial fertilizer to corn at rates to achieve yield goals expected under conditions of full irrigation. Cattle manure and ammonium nitrate were applied in 2002 at the University of Nebraska rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 17 publications
4
26
1
3
Order By: Relevance
“…In addition to the N uptake pattern, the irrigation regime during the different seasons determined soil N min levels in the rooting zone and had a large effect on N fertilizer recommendations. Low irrigation rates were applied during the later fruiting period in the AW season in contrast to the WS season, and this would have reduced the risk of nitrate leaching out of the root zone and therefore unavailable for crop growth during irrigation (Nakamura et al, 2004;Tarkalson et al, 2006). N supply strategies during the AW seasons are therefore distinct from those in the WS seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the N uptake pattern, the irrigation regime during the different seasons determined soil N min levels in the rooting zone and had a large effect on N fertilizer recommendations. Low irrigation rates were applied during the later fruiting period in the AW season in contrast to the WS season, and this would have reduced the risk of nitrate leaching out of the root zone and therefore unavailable for crop growth during irrigation (Nakamura et al, 2004;Tarkalson et al, 2006). N supply strategies during the AW seasons are therefore distinct from those in the WS seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that crop yields generally are similar between manure and synthetic fertilizers when applied to meet crop N requirements (Stevenson et al 1998;Eghball and Power 1999b;Basso and Ritchie 2005;Tarkalson et al 2006). Sneller and Laboski (2009) found no difference in corn (Zea mays L.) yield between manure types and synthetic fertilizer.…”
Section: Barley Silage Yieldmentioning
confidence: 99%
“…Irrigation can increase the potential risk of nitrate N leaching (Power and Schepers 1989), particularly when manure is applied to irrigated land (Chang and Janzen 1996;Davis et al 1997). Tarkalson et al (2006) showed leaching of nitrate from manure and synthetic fertilizer occurred under deficient irrigation, but was 15 to 47% less than under full irrigation. Chang and Janzen (1996) compared excess manure application under rainfed and irrigated conditions in southern Alberta.…”
Section: Soil Nitrogenmentioning
confidence: 99%
See 2 more Smart Citations